Salmonella in Portuguese autochthonous hens breeds: a One Health concern - Miranda, C.; Ribeiro, V.; Dantas, R.; Brito, N. V. (Scientific Letters, 2023)
<span class="NormalTextRun SCXW144570251 BCX2" data-ccp-parastyle="SL_1.6_abstract" data-ccp-parastyle-defn=""ObjectId":"a5e127f2-8edc-40ef-a1e9-bee6bfd598d1|120","ClassId":1073872969,"Properties":[469775450,"SL_1.6_abstract",201340122,"2",134234082,"true",134233614,"true",469778129,"SL16abstract",335572020,"1",469777841,"Times New Roman",469777842,"Times New Roman",469777843,"Times New Roman",469777844,"Times New Roman",469769226,"Times New Roman",335551500,"0",335559704,"1033",335559705,"1031",335551547,"1033",335559685,"1701",335559737,"401",335559740,"260",201341983,"2",335559738,"240",335551550,"6",335551620,"6",469775498,"Normal"]">Background: The genus Salmonella is characterized as an enteric pathogen of mammals, reptiles, and birds and one of the most adapted environmental pathogens. These bacteria cause a high number of foodborne salmonellosis annually as a result of eating eggs, poultry and raw or undercooked meat contaminated with Salmonella [1,2]. Food-producing animals, in particular chickens, are considered reservoirs of this agent, associated with clinical illness and enormous risk to humans by the food chain. On the opposite, the local breeds in extensive or semi-extensive systems work to mitigate the impacts of intensive farming systems on food safety and public health, and enhance the rural economies. However, the studies on pathogen agents in local breeds are scarce [2,3]. Objective: The aim of this study was to determine the presence of Salmonella spp. in four Portuguese autochthonous chicken breeds in semi-extensive systems. Methods: A total of 87 samples of eggshells were obtained from 30 hens farms (2 to 4 samples/farm) of the following autochthonous breeds: “Pedrês Portuguesa” (n=22), “Amarela” (n=20), “Preta Lusitânica” (n=23) and “Branca” (n=22), in six different regions of Portugal during February of 2023. The Salmonella microbiological isolation was performed by the standard method recommended by ISO 6579:2017. Each sample was pre-enriched in Buffered peptone water, followed by incubation in Modified semi-solid Rappaport-Vassiliadis medium supplemented with novobiocin. From the culture obtained, selective solid media are inoculated: Chromagar Salmonella Plus agar®; Xylose lysine deoxycholate agar® and Salmonella-Sighella agar®. Results: From the four analyzed autochthonous hen breeds, no growth of characteristic Salmonella colonies was observed in the used selective solid media. Conclusions: To the best of our knowledge, this is the first study based on these autochthonous breeds, although the number of samples is limited. These preliminary results suggested that hen’s eggs are not the most important vehicle of the infection by Salmonella, indicating a positive impact on animal health and public health.